Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1063/1.341489
|View full text |Cite
|
Sign up to set email alerts
|

The formation of hydrogen passivated silicon single-crystal surfaces using ultraviolet cleaning and HF etching

Abstract: We have tried to develop a new procedure to prepare the clean surface of a silicon single crystal. We successfully prepared the contamination free bare silicon surface with ultraviolet cleaning followed by HF dipping with low concentration HF obtained by dilution by organic free ultrapure water, at room temperature under the atmospheric condition. X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, and ultraviolet photoelectron spectroscopy measurements proved thus prepared surface has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
172
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 505 publications
(187 citation statements)
references
References 31 publications
9
172
0
Order By: Relevance
“…We observed that the thickness of the organic layer is directly correlated with the intensity of the dissipation peak in figure 6. The peak is also seen for the native oxide-covered device and for similar diamond and SiN devices (see [7] and supporting information), where it may be explained by a physisorbed molecular layer, possibly hydrocarbons [43]. The adventitious surface layer is small for all other devices, because they only experienced short air Figure 6.…”
Section: Temperature Dependence Of Dissipationmentioning
confidence: 94%
“…We observed that the thickness of the organic layer is directly correlated with the intensity of the dissipation peak in figure 6. The peak is also seen for the native oxide-covered device and for similar diamond and SiN devices (see [7] and supporting information), where it may be explained by a physisorbed molecular layer, possibly hydrocarbons [43]. The adventitious surface layer is small for all other devices, because they only experienced short air Figure 6.…”
Section: Temperature Dependence Of Dissipationmentioning
confidence: 94%
“…Followed by aqueous rinsing, passivation by fluoride ͑F − ͒ can be potentially removed to render the surface hydrophilic via the exchange of fluorine with OH − groups. 14,15 Researchers have been able to reduce S contamination on surfaces up to few atomic percent with controlled oxide growth. 10 The addition of a low concentration of HF into the HNO 3 solution ͑known as SE, slight etch͒ controls oxide growth by competitive oxidation and etching together.…”
mentioning
confidence: 99%
“…It is important to keep in mind, that in XPS, the photoelectrons are collected from a so called escape depth, which varies with the electron energy. For our experimental conditions, the escape depth may be estimated as (15-30) A, or (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) monolayers of silicon in the (100) crystallographic direction [8]. Thus, atomic concentrations presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to this study, a silicon surface polished by colloidal silica is predominately covered by dihydride species, a significant fraction of which is backbonded to oxygen. Such a chemical structure of the silicon top layer resembles an early stage of silicon native oxidation [11,19,20].…”
Section: Thickness Of Silicon Oxide Layermentioning
confidence: 99%